2021
DOI: 10.7717/peerj.10571
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial meta-analysis of chicken cecal microbiota

Abstract: Poultry production is an industry that generates 90,000 metric tons of chicken meat worldwide. Thus, optimizing chicken growth and sustainable production is of great importance. A central factor determining not only production parameters, but also stability of the immune system and chicken health, is the diversity and variability of the microbiota present throughout the gastrointestinal tract. To date, several studies have investigated the relationship between bacterial communities and the gut microbiome, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…Results from the 16S-rRNA gene sequencing and subsequent microbiome analysis revealed that Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria were the most abundant phyla, which is consistent with the pre-established literature regarding the composition of chicken microbiomes in the cecum [42,43]. These phyla persisted as the most abundant across timepoints and treatments, though they did experience changes in the percentages of the abundance ratios within each group that were time and treatment dependent.…”
Section: Discussionsupporting
confidence: 85%
“…Results from the 16S-rRNA gene sequencing and subsequent microbiome analysis revealed that Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria were the most abundant phyla, which is consistent with the pre-established literature regarding the composition of chicken microbiomes in the cecum [42,43]. These phyla persisted as the most abundant across timepoints and treatments, though they did experience changes in the percentages of the abundance ratios within each group that were time and treatment dependent.…”
Section: Discussionsupporting
confidence: 85%
“…The samples of the present study were collected from 25- to 28-days old birds, which falls within the former range, and shows beneficial effects of the P(OA + EO) supplementation for antibiotic-free chickens. According to a bacterial meta-analysis of the cecal microbiota of chickens, Coprobacillus , even though in a small abundance, has been found in most of the analyzed studies ( Chica Cardenas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although bacterial relative abundances are known to vary across studies [48], Firmicutes was found to be the most abundant phylum and Lactobacillus the most abundant genus, as was reported in a recent meta-analysis [49], although in different percentages. The composition of fecal microbiota samples obtained via cloacal swabs or directly from the caecum were different, as observed by others [50][51][52].…”
Section: Descriptive Analyticsmentioning
confidence: 55%